Implementasi Metode Analisis Bahasa Dalam Pembelajaran Ketrampilan Membaca Teks Arab di UNIDA Gontor - Mandrasi Amira Saidah; Muhammad Syamsul Arifin; Riza Nurlaila (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2021)
Arabic teaching-learning is essential for social communication needs as well. It is a language in which al-Qur’an and Hadith became the primary source of all knowledge. Reading skill mastery included reading Arabic text, which is compulsory because it contributes to improving receptive skills that need adequate vocabulary and syntactic comprehension for good reading. This research proposed to elaborate teaching implementation of Arabic text reading using ‘linguistic analysis’ to conduct it using a descriptive method. The study resulted that the teaching Arabic text reading at the University of Darussalam Gontor used taught in five steps as follows: Short explanation about three features of Arabic linguistic analysis (I’rab): function (mauqi’), declension (hukm), and the sign of declension (‘alāmah), Determining kind of sentence (nominal or verbal) to determine functions of each word of the sentence, Determining and organizing those functions into a subject, predicate and complement to determine their declension, Determining signs of declension based on their declensions and word category (shinfu’l kalimah), Determining attachment of reduction (muta’allaq al-jarr al-ashli) and declension in place (I’rab mahalli).